2021
DOI: 10.3389/fmicb.2021.699927
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antimicrobial Resistance, Virulence Genes, Phylogroups, and Biofilm Formation of Escherichia coli Isolated From Intensive Farming and Free-Range Sheep

Abstract: Pathogenic E. coli are among the most frequently isolated bacterial pathogens on large-scale sheep farms in China. Antibiotic use in wool sheep production is a risk factor for promoting the emergence of resistant E. coli. To reveal the differences of E. coli populations in sheep from different farming systems the antimicrobial resistance, virulence genes, biofilm formation, and phylogroups of 500 E. coli isolates obtained between September 2019 and December 2020 in northwest China from diarrheic infections of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…It may be that the virulence genes carried by different STs or CCs differed. There are 16 virulence genes which represent the main categories of virulence determinants, including adhesins ( sfa , pap C, sep A, etr A, aer , fea G, fsa A, and eae A), capsule synthesis ( rfc ), and toxins ( cnf 1, hly A, elt A, est A, exh A, stx 1, and stx 2) ( Zhao et al, 2021 ). They divided E. coli into intestinal pathogenic E. coli (IPEC) and extraintestinal pathogenic E. coli (ExPEC) ( Habouria et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It may be that the virulence genes carried by different STs or CCs differed. There are 16 virulence genes which represent the main categories of virulence determinants, including adhesins ( sfa , pap C, sep A, etr A, aer , fea G, fsa A, and eae A), capsule synthesis ( rfc ), and toxins ( cnf 1, hly A, elt A, est A, exh A, stx 1, and stx 2) ( Zhao et al, 2021 ). They divided E. coli into intestinal pathogenic E. coli (IPEC) and extraintestinal pathogenic E. coli (ExPEC) ( Habouria et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 67 E. coli strains were isolated from a previous study ( 17 ). Briefly, these isolates were collected from cloacal swabbing of sheep in Shaanxi, Ningxia, Inner Mongolia, and Qinghai of China between 2019 and 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, birds and dolphins might also play a key role in the development and intercontinental dissemination of ESBLs ( 15 , 16 ). Among resistant E. coli isolates of animal origin, those from sheep have long been neglected, although a few previous studies have reported resistant E. coli from sheep ( 17 ). However, phenotypic and genotypic characterization of the E. coli isolates and the antibiotic resistance genes (ARGs) they carry in diarrheic sheep remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The biofilm formation capacity of the isolate was measured by staining with 0.1% crystal violet as previously described with minor modifications. 19 The plates were incubated at 37°C for 24 h, washed, fixed, stained, and solubilized with 95% ethanol. Subsequently, the absorbance was measured at 570 nm with a microplate reader (PerkinElmer, USA).…”
Section: Methodsmentioning
confidence: 99%